Influence of Price And Location on Belikopi Ploso Consumer Purchasing Decisions - Syaidah, Ainun; Munawaroh, Munawaroh; Susilowati, Lina (PT. Riset Press International, 2023)
The aim of this study is to figure out how location and pricing affect consumer buying decisions in Belikopi Ploso. This study uses a quantitative methodology that uses a variety of linear regression analytic techniques. The population of the study consisted of all Belikopi Ploso clients. the Lemeshow formula-based sample of 100 people. The information was gathered using a questionnaire using a Linkert scale. The research data passed the tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. A significance value of t of 0.00 0.05 and the study's findings showed that 1) pricing significantly influenced Belikopi Ploso consumers' buying decisions, 2) The location has had a considerable impact on Belikopi Ploso consumers' purchase decisions, according to the t significance value of 0.044 0.050. 3) The F significance value of 0.00 0.05 showed that price and location both significantly affecedt the purchasing decisions of Belikopi Ploso consumers.